2020
DOI: 10.3329/jbsp.v14i2.44789
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic impairment and oxidative stress: Relationship in PCOS patients

Abstract: Background: Polycystic ovary syndrome (PCOS) is one of the most common, heterogeneous endocrine disorder of reproductive aged women. Association of autonomic impairment and elevated oxidative stress may predispose these patients to increased cardiovascular risks. Objective: To evaluate the relationship between cardiac autonomic nerve function (CANF) and oxidative stress in patients with PCOS. Methods: This cross sectional study was conducted in Department of Physiology, Bangabandhu Sheikh Mujib Med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
1
1
0
Order By: Relevance
“…The negative correlation between HR and platelet of FIV-infected cats in the present study was in accordance with the report of Ozdemir et al (2004), who found that the autonomic nervous system had in- fluence on the changing of platelet profile. Moreover, the negative correlation between HR and MDA of FIV-infected cats in the present study was similar to the study of Mostafa et al (2019). They found that the mean HR was negatively correlated with MDA level.…”
Section: Discussionsupporting
confidence: 90%
“…The negative correlation between HR and platelet of FIV-infected cats in the present study was in accordance with the report of Ozdemir et al (2004), who found that the autonomic nervous system had in- fluence on the changing of platelet profile. Moreover, the negative correlation between HR and MDA of FIV-infected cats in the present study was similar to the study of Mostafa et al (2019). They found that the mean HR was negatively correlated with MDA level.…”
Section: Discussionsupporting
confidence: 90%
“…CAT enzyme hydrolyzes H2O2 into H2O and 1/2 O2. This enzyme has an important role in protecting DNA, proteins, and cellular lipids (39). NO is a very useful mediator in some physiological and biologic pathways in the human body.…”
Section: Resultsmentioning
confidence: 99%